1. LITERATURE REVIEW: THE ROLE OF WORK ENGAGEMENTAND EMPLOYEE AGILITY ON THE QUALITYOF IMMIGRATION SERVICES - Maharani Yuniko Susanti; Habbi Firlana; Pascalis Danny Kristi Wibowo; Nur Priyanto; Suroso; Anwar Hendro; Tutidikatama; Andri Gandhy (Staf Komunikasi dan Elektronika, TNI Angkatan Udara, 2026)
This study aims to analyze the relationship between employee agility and workengagement, as well as their implications for the quality of immigration services, using aliterature review approach. Technological advancements, digital transformation, and risingpublic expectations regarding public services require organizations—including immigrationagenciesto possess a workforce that is both adaptive and highly engaged. Employee agilityand work engagement are identified as key factors in enhancing service quality. The researchemploys a literature review method, examining five scholarly articles published between 2024and 2025 that were selected based on their relevance to the research topic. Data wereanalyzed descriptively through the identification, categorization, and synthesis of findings fromprevious studies. The review indicates that work engagement contributes positively toenhancing employee agility, while employee agility is influenced by various factors such asorganizational support, leadership, digital competence, and human resource managementpractices. The synthesis further reveals that employees with high work engagement and strongadaptability have the potential to deliver services that are more effective, responsive, andoriented toward public needs. The study concludes that employee agility and work engagementare crucial factors in improving the quality of immigration services. This research contributes ascholarly synthesis of the relationship between these two variables, serving as a conceptualfoundation for future empirical research and as a reference for formulating human resourcemanagement strategies within immigration agencies.